Déjà Vu Herhaling in culturen wereldwijd - Houppermans, Sjef (LUP Academic, 2011)
Repetition has a major role in human culture. In lullabies and prayers, in protests and war cries: from the cradle to the grave, repetition is the companion to life's essentials. In a constantly revolving world there is no pure repetition. Events never repeat themselves precisely. This is equally true of repetition in Literature and Art, where the use of repetition is varied and frequent. How does repetition work? And how can it be of use? Déjà Vu unravels these questions in fifteen chapters ranging from film remakes and Baudelaire to the offer of Abraham and David Lodge, Small World. Déjà Vu shows that repetition has been used worldwide through all times and cultures in visual arts, poetry, music, literature and motion pictures.